2015
DOI: 10.1186/1756-8935-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment of methylation maintenance is the major cause of DNA methylation reprogramming in the early embryo

Abstract: BackgroundDNA methylomes are extensively reprogrammed during mouse pre-implantation and early germ cell development. The main feature of this reprogramming is a genome-wide decrease in 5-methylcytosine (5mC). Standard high-resolution single-stranded bisulfite sequencing techniques do not allow discrimination of the underlying passive (replication-dependent) or active enzymatic mechanisms of 5mC loss. We approached this problem by generating high-resolution deep hairpin bisulfite sequencing (DHBS) maps, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 44 publications
(82 reference statements)
12
137
0
2
Order By: Relevance
“…These findings indicated that, contrary to what had been proposed , the imprint erasure is initiated in early mPGCs and the demethylation can be explained largely by a replication-coupled passive mechanism. Consistent with this report, independent studies for the methylation states of the repetitive elements in mPGCs by highthroughput hairpin bisulfite sequencing demonstrated the prevalence of hemimethylated DNA in mPGCs, indicating that the replication-coupled passive demethylation is a major mechanism for genome-wide DNA demethylation in mPGCs (Seisenberger et al 2012;Arand et al 2015). Accordingly, mPGCs lacking TET1, an active DNA demethylase and the only TET protein expressed at a high level in mPGCs, undergo genome-wide DNA demethylation in an apparently normal fashion (Dawlaty et al 2011).…”
Section: Genome-wide Dna Demethylation During Germ Cell Developmentsupporting
confidence: 74%
“…These findings indicated that, contrary to what had been proposed , the imprint erasure is initiated in early mPGCs and the demethylation can be explained largely by a replication-coupled passive mechanism. Consistent with this report, independent studies for the methylation states of the repetitive elements in mPGCs by highthroughput hairpin bisulfite sequencing demonstrated the prevalence of hemimethylated DNA in mPGCs, indicating that the replication-coupled passive demethylation is a major mechanism for genome-wide DNA demethylation in mPGCs (Seisenberger et al 2012;Arand et al 2015). Accordingly, mPGCs lacking TET1, an active DNA demethylase and the only TET protein expressed at a high level in mPGCs, undergo genome-wide DNA demethylation in an apparently normal fashion (Dawlaty et al 2011).…”
Section: Genome-wide Dna Demethylation During Germ Cell Developmentsupporting
confidence: 74%
“…With respect to the ConsensusPathDB results, EGFR1 signaling has been implicated in chronic bronchitis 22 and WNT signaling is involved in the pathogenesis of lung development, COPD, 23 and asthma. 24 Differential methylation in multiple sites across a defined genomic region may reveal more biological relevance than single CpG associations, and in contrast to previous methods, such as bump hunting, that are agnostic to genomic annotation, 25,26 we defined regions using multi-site associations for annotated genes. Among these multi-site genes, 3 are of particular interest: CHRM1, as it was the top result among 10% b-diff results; ESM1, a gene mainly expressed in the endothelial cells in human lung and kidney tissues 27 ; and PITPNM1, a gene found within a linkage disequilibrium block surrounding the susceptibility gene identified in a previous association study of childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the unresolved issue of how meaningful peripherally derived methylation patterns are with respect to brain activity and consequently behavior and psychiatric risk remains controversial. Epigenetic changes are highly tissue specific and only a subset of DNA methylation changes show cross-tissue correlation between peripheral tissues and the brain (Davies et al, 2012; Farré et al, 2015; Hannon et al, 2015). Taken together, it would be premature to draw general conclusions from the reported findings.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%